Design and testing of an efficient and compact piezoelectric energy harvester - (:unkn) unknown (ELSEVIER SCI LTD, 2011)
Piezoelectric materials generate electricity when they are subjected to dynamic strain. In this paper compact size self contained energy harvesters were built by considering typical space available for AA size batteries. Each of the harvesters contains a rectifier circuit with four diodes and a capacitor. A series of piezoelectric energy harvesters with circular and square cross-sections were built and tested at different frequency and amplitude levels. On 1 M Omega impedance digital oscilloscope, it was observed that the voltages reached to 16 V (round cross-section) and 25 V (square cross-section) at 50 Hz frequency. The highest power output accomplished was 625 mu W. The outputs of both types of the harvesters were very similar at low amplitudes. However, the square cross-section facilitates better attachment of the piezoelectric elements with the harvester shell and worked efficiently at higher amplitudes without immediate failure. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Piezoelectric energy; Microenergy harvester; Piezoelectric battery; SCAVENGERS; SYSTEMS; BENDER